2016
DOI: 10.18196/jmmr.5103
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Mutu Rekam Medis Di Rs Pku 1 Muhammadiyah Yogyakarta: Studi Kasus Pada Pasien Sectio Caesaria

Abstract: Beberapa studi mengungkapkan ketidaklengkapan dokumen rekam medis, tulisan dokter yang sulit terbaca dan pengelolaan yang terkesan seadanya. Begitu juga di Rumah Sakit PKU Muhammadiyah Yogyakarta dimana pengelolaan rekam medis ada kendala antara lain kurang lengkapnya dokter dalam pengisisan rekam medis. Penelitianinimerupakan jenis penelitian deskriptif kualitatif dengan rancangan studi kasus. Subyek penelitian adalah dokter, Manajer pengendalian mutu rekam medis, dan supervisor pengolahan data di unit rekam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 2 publications
0
7
0
7
Order By: Relevance
“…This was because sometimes the officer waited for medical records of other patients who were still undergoing hospitalization to be returned together to the Medical Record Unit. 7 Rahayu et al (2016) argues that health personnel involved in the medical records consist of interdisciplinary professions such as doctors, nurses, pharmacists, laboratory workers, and others. 15 Pamungkas and Hariyanto (2015) conducted a study at general hospital of Ngudi Waluyo Wlingi and found that the main cause of incomplete medical record file was inability of the doctor when filling the medical record file because the doctor prioritizes the service so that he does not have enough time to complete the medical record file.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was because sometimes the officer waited for medical records of other patients who were still undergoing hospitalization to be returned together to the Medical Record Unit. 7 Rahayu et al (2016) argues that health personnel involved in the medical records consist of interdisciplinary professions such as doctors, nurses, pharmacists, laboratory workers, and others. 15 Pamungkas and Hariyanto (2015) conducted a study at general hospital of Ngudi Waluyo Wlingi and found that the main cause of incomplete medical record file was inability of the doctor when filling the medical record file because the doctor prioritizes the service so that he does not have enough time to complete the medical record file.…”
Section: Resultsmentioning
confidence: 99%
“…The medical record unit and medical staff are responsible for the management of the medical records which involve the completeness of content, storage policies, destruction and confidentiality, ownership, utilization and organization. 7 Medical record documents in hospitals have the purpose of supporting the achievement of orderly administration to improve the quality of health services in hospitals. 8 The contents of the patient's medical records are sources of information about the patient's medical history.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the process of documentation often faces obstacles. Pasaribu, Sihombing, 2017, Hutama, Santosa, 2016, and Yusuf et al, 2017, found that average rate of incomplete documentation in conventional method recording was at 36.8%, thus it can slow down the process of reporting, the process of searching the data of the patients, and it takes a many storages or a large room to save the patients' documents (Hutama & Santosa, 2016;Pasaribu & Sihombing, 2017;Yusuf et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Midwifery documentation, particularly in family planning case is still written in paper-based. This method may face several barriers such as it takes a lot of time to record, the data may invalid, inaccuracy of documentation, the slow process in searching the acceptors' data which cause the health service for patient become slow and less optimal, take many storages to save the documentation in paper-based, often missing and not found (Hutama & Santosa, 2016;Pasaribu & Sihombing, 2017;Torry, Koeswo, & Sujianto, 2016).…”
Section: Introductionmentioning
confidence: 99%